The influence of physical fitness and nutritional status on students' learning outcomes - Yeni Ambar Wati; Hendri Neldi; Wilda Welis; Alnedral Alnedral (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Floor gymnastics learning at SMAN 1 Siberut Barat Daya faces several challenges, including low student skill levels, limited facilities, and the constraints of a 3T (frontier, outermost, and disadvantaged) school context. This study aimed to develop and examine the feasibility and effectiveness of a Kurikulum Merdeka–based floor gymnastics teaching module. The study employed a research and development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were 47 Grade X students. Data were collected through gymnastics skill tests, observations, questionnaires, and interviews, and analyzed using descriptive statistics and paired sample t-tests. The results showed significant improvements in students’ performance on forward roll, backward roll, and candlestick movements after using the module (p < 0.001). Expert validation and student responses indicated that the module is valid, practical, and suitable for use in schools with limited resources.